Coral Reefs of the High Seas: Hidden Biodiversity Hotspots in Need of Protection - Wagner, Daniel; Friedlander, Alan M.; Pyle, Richard L.; Brooks, Cassandra M.; Gjerde, Kristina M.; Wilhelm, T. ‘Aulani (Frontiers in Marine Science, 2020)
Coral reefs are widely regarded as one of the top science and conservation priorities globally, as previous research has demonstrated that these ecosystems harbor an extraordinary biodiversity, myriad ecosystem services, and are highly vulnerable to human stressors. However, most of this knowledge is derived from studies on nearshore and shallow-water reefs, with coral reef ecosystems remaining virtually unstudied in marine areas beyond national jurisdiction (ABNJ), commonly known as the high seas. We reviewed information on the spatial distribution of reef-building corals throughout their depth range, and compiled a total of 537,782 records, including 116 unique records from ABNJ at depths between 218-5,647 m. The majority of reef-building coral records in ABNJ were in association with geomorphological features that have steep topographies. These habitats, which include escarpments, seamounts, and submarine ridges accounted for >74% of the records in international waters. Such geomorphological features, particularly those that occur within close proximity to the sea surface, should be prioritized for future scientific exploration. The majority of the reef-building coral records in ABNJ (>77%) were recorded in unprotected waters, and this study discusses the challenges and opportunities for protecting marine biodiversity in ABNJ. Finally, this study offers a definition of high seas coral reefs, and provides a framework to better understand and conserve these fragile ecosystems.